The use of chemotherapeutics for the treatment of keloid scars - Christopher David Jones; Luke Guiot; Mike Samy; Mark Gorman; Hamid Tehrani (PAGEPress Publications, 2015)
Keloid scars are pathological scars, which develop as a result of exaggerated dermal tissue proliferation following cutaneous injury and often cause physical, psychological and cosmetic problems. Various theories regarding keloidogenesis exist, however the precise pathophysiological events remain unclear. Many different treatment modalities have been implicated in their management, but currently there is no entirely satisfactory method for treating all keloid lesions. We review a number of different chemotherapeutic agents which have been proposed for the treatment of keloid and hypertrophic scars while giving insight into some of the novel chemotherapeutic drugs which are currently being investigated. Non-randomized trials evaluating the influence of different chemotherapeutic agents, such as 5-fluorouracil (5-FU); mitomycin C; bleomycin and steroid injection, either alone or in combination with other chemotherapeutic agents or alternative treatment modalities, for the treatment of keloids were identified using a predefined PubMed search strategy. Twenty seven papers were identified. Scar improvement ≥50% was found in the majority of cases treated with 5-FU, with similar results found for mitomycin C, bleomycin and steroid injection. Combined intralesional 5-FU and steroid injection produced statistically significant improvements when compared to monotherapy. Monotherapy recurrence rates ranged from 0-47% for 5-FU, 0-15% for bleomycin and 0-50% for steroid injection. However, combined therapy in the form of surgical excision and adjuvant 5-FU or steroid injections demonstrated lower recurrence rates; 19% and 6% respectively. Currently, most of the literature supports the use of combination therapy (usually surgery and adjuvant chemotherapy) as the mainstay treatment of keloids, however further investigation is necessary to determine success rates over longer time frames. Furthermore, there is the potential for novel therapies, but further investigation is required to elucidate their true efficacy.